La importancia de la TAC en la educación y cambios sociales - Victor Manuel Amar Rodríguez (Universidad de Cádiz, 2017)
The debate must always be healthy and even an incentive to know and improve. In our case, we will establish it in different areas that will be extended to the broader framework of education and technologies. Therefore, from the people to the tools will be reasons to stop us to reflect and, equally, a pretext to share desires for improvement, because in the twenty-first century it becomes inconceivable to teach or educate without the technologies of the present. However, the conclusions are presented in continuous construction as we encourage the need for a willingness to be continuously predisposed to technological changes and their ideal inclusion in education.